A Disclosure of Reading Rate and Its Effect on Comprehension in Second Language Learning Context: Pengungkapan Tingkat Membaca dan Pengaruhnya terhadap Pemahaman dalam Konteks Pembelajaran Bahasa Kedua - Rawian, Rafizah Mohd; Mokhtar, Ahmad Azman; Yahaya, Mohamad Fadhili (JEES (Journal of English Educators Society), 2018)
In reading, it is vital for readers to develop decoding to the extent where each word is recognized automatically. Once this happens, they will have the necessary attention to focus on the sense or meaning of the text. This study investigated adult ESL learners’ reading rate and its relationship with comprehension. This study also examined possible differences in the reading rate in terms of gender and academic semester. Its respondents were 210 Diploma students from one of the universities in Malaysia. Data were collected through Oral Reading Fluency (ORF) Assessment and Reading Comprehension Test. Jameson’s (2005) Reading Rate Formula and Levels of Reading Rate for College Readers were used to examine respondents’ reading rate. All data were coded and computer-scored using the Statistical Package for the Social Science (SPSS) programme. This study revealed that 106 respondents were Excellent College Readers while the rest ranged from Strong College Readers to Good General Readers. It was also discovered that females performed better than males in reading rate and Semester 3 respondents’ reading rate was better than those in Semester 1. The correlation test indicated positive relationship between reading rate and comprehension.